SENTIMENT ANALYSIS ON SIKSA KUBUR MOVIE REVIEWS: A COMPARATIVE STUDY BETWEEN NAÏVE BAYES AND SUPPORT VECTOR MACHINE METHOD - Linda Handayani; Andariza Permana (STKIP PGRI Tulungagung, 2026)
This study examines user reviews of application X about the film Siksa Kubur by Joko Anwar which was released in 2024. The purpose of this study is to conduct user sentiment analysis and compare the results of sentiment analysis using the naïve bayes method and support vector machine based on training data scenarios and test data. The data collected through tweet harvest using the Python script on google colab is 3450 containing